The Impact of Science Curriculum in Reducing Pollution: Evidence from a University in Saudi Arabia - Saad Alshehri (Science Education International, 2025)
This study seeks to explore, through practical means, the holistic impact of the science curriculum (SC) in heightening awareness about pollution-related issues. In addition, it aims to assess its role in motivating a particular behavior among higher education students in Saudi Arabia specifically, the actions they take to mitigate pollution. The study adopted a conclusive research design and used a survey to collect quantitative data. The rationale for using the survey method was applied to analyze the relationship between the study constructs and verify the hypothesis based on the responses. Atotal of 182 students studying in various science disciplines, randomly selected from a higher educational institution in Saudi Arabia, responded to a survey. The results provide strong evidence that SC can promote a greater level of awareness of the effects of pollution. The findings offer concrete evidence backing the idea that the SC plays a mediating role in pollution reduction. Furthermore, they imply that education has a comparatively weaker influence on the pro-environmental behaviors or actions of students. This study will have significant value for higher educational institutions as it provides empirical evidence that SC can increase awareness of the effects of pollution, stimulating pro-environmental behaviors and in reaching sustainable development.